THE FEATURES FOR PLANNING AN EFFECTIVE TEACHER TRAINING ON THE VIRTUAL PLATFORM - Izabella Gravikovna Babayan; Alesa Misakovna Durgaryan (International Journal of Innovative Technologies in Social Science, 2022)
Modern technology offers today’s teachers many different methods to improve and develop their professional knowledge and skills. Due to them it is available to take part in the different trainings on the virtual platform using modern technologies as additional basements for their professional development. The situation in the world today has completely changed not only the nature and structure of the educational process in schools and other educational institutions, but also the teachers' completely different requirements to carry out the educational process online. In order to make the educational process more effective, teachers not only change their curricula and work style, but also change the materials and methods they use to fit the online platform. The latter, in turn, promotes the acquisition and application of many new knowledge and skills. There are various online programs and tools in the media field today to make online learning more effective. Virtual training is considered to be one of the most prominent and necessary method of teacher training which is quickly spreading all over the world. All of these virtual training opportunities give a chance to keep in touch with fellow teachers from around world. Teachers can share their experience and knowledge and get advice on different teaching problems and difficulties. In addition, virtual training is always updated and includes the latest changes and approaches to the teaching sphere.